Preschool Children’s Speech Pedagogical Sound Culture Correction - Borova, Valentyna Ye.; Artemova, Liubov V.; Melnyk, Nataliia I.; Benera, Valentuna Ye.; Malinovska, Nataliia V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: The article aims to reveal the features of correction of the sound culture of the preschool-age children’s speech, the effectiveness of which has been tested experimentally. Background: The sound culture of speech is a multicomponent formation, which covers the phonetic correctness of speech; general language skills and orthoepic correctness of speech. Pedagogical correction of the sound culture of speech is focused on the correct the errors caused by a violation of the sound articulation, sound pronunciation, orthoepic norms of pronunciation, voice strength, etc. Method: In the study, the author’s method of pedagogical correction of the sound culture of children’s speech was used. Also, it was used comparative analysis and method of successive analysis of adjustment variants of the speech sound culture. Results: An individual model of pedagogical correction of the sound culture of the child’s speech was developed. Training to deepen knowledge, improvement of abilities, and skills of teachers were held. The exercises in sound pronunciation and intonational speech expressiveness were developed. Conclusion: Positive dynamics of developmental levels of the sound culture of children’s speech, which has been confirmed by the results of quantitative and qualitative analysis, confirms the effectiveness of the experimental methods of pedagogical correction of the sound culture of speech.